2022
DOI: 10.1001/jamaoncol.2021.7366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capecitabine Maintenance Therapy Plus Best Supportive Care vs Best Supportive Care Alone on Progression-Free Survival Among Patients With Newly Diagnosed Metastatic Nasopharyngeal Carcinoma Who Had Received Induction Chemotherapy

Abstract: IMPORTANCE Capecitabine maintenance therapy improves survival outcomes in various cancer types, but data are limited on the efficacy and safety of capecitabine maintenance therapy in metastatic nasopharyngeal carcinoma (NPC).OBJECTIVE To investigate the efficacy and safety of capecitabine maintenance therapy in metastatic NPC. DESIGN, SETTING, AND PARTICIPANTSThis randomized phase 3 clinical trial was conducted at Sun Yat-sen University Cancer Center from May 16, 2015, to January 9, 2020, among 104 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…One study suggested that the first three years after chemoradiotherapy are the highest incidence time of treatment failure ( 23 ). In another study associated with metastatic NPC, the median follow-up duration was 33.8 months, and the results showed that capecitabine maintenance could increase the chances of survival ( 24 ). However, it is still unclear whether the perfect duration of metronomic treatment is one year or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study suggested that the first three years after chemoradiotherapy are the highest incidence time of treatment failure ( 23 ). In another study associated with metastatic NPC, the median follow-up duration was 33.8 months, and the results showed that capecitabine maintenance could increase the chances of survival ( 24 ). However, it is still unclear whether the perfect duration of metronomic treatment is one year or not.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether the perfect duration of metronomic treatment is one year or not. Thus, we used the structural sensitivity analysis and extended the metronomic capecitabine treatment time by three years based on the published studies ( 23 , 24 ). The ICER of metronomic capecitabine versus observation was $12,214.37 per QALY.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, a phase III randomized controlled clinical study on the maintenance treatment of patients with newly diagnosed metastatic NPC with capecitabine was published. 15 In total, 104 patients newly diagnosed with metastatic NPC were included in that study. All patients were 1:1 randomly assigned to the capecitabine maintenance group (1000 mg/m 2 , b.i.d., d1-14, Q3W) or the best supportive treatment group after receiving four to six cycles of paclitaxel, cisplatin, and capecitabine induction chemotherapy.…”
Section: 12mentioning
confidence: 99%
“…Capecitabine maintenance therapy has been shown to improve oncological outcomes in high‐risk subgroups of locally advanced NPC, but its application in metastasis still lacks high‐quality evidence. In 2022, a phase III randomized controlled clinical study on the maintenance treatment of patients with newly diagnosed metastatic NPC with capecitabine was published 15 . In total, 104 patients newly diagnosed with metastatic NPC were included in that study.…”
Section: Advances In Systemic Treatment Of Recurrent And/or Metastati...mentioning
confidence: 99%
“…In NPC, moreover, a phase 3 randomized clinical trial (NCT02460419) provided evidence supporting the efficacy of capecitabine maintenance therapy as a first-line treatment for mNPC (26). This trial randomized patients with newly diagnosed mNPC who achieved disease control after 4-6 cycles of induction chemotherapy to receive either capecitabine maintenance therapy plus best supported care (CBSC) or best supported care (BSC) alone (26). Patients in the CBSC group had a significantly higher median PFS survival compared to the BSC group (35.9 vs. 8.2 mo, HR 0.44, 95% CI 0.26-0.74, P = 0.002) (26).…”
Section: Introductionmentioning
confidence: 99%